Inhibin B Response to Testicular Toxicants Hexachlorophene, Ethane Dimethane Sulfonate, Di‐(n‐butyl)‐phthalate, Nitrofurazone, DL‐Ethionine, 17‐alpha Ethinylestradiol, 2, 5‐Hexanedione, or Carbendazim Following Short‐Term Dosing in Male Rats. (24th January 2013) - Erdos, Zoltan; Pearson, Kara; Goedken, Michael; Menzel, Karsten; Sistare, Frank D.; Glaab, Warren E.; Saldutti, Louise Parks
<x xml:space="preserve">Abstract</x> BACKGROUND Inhibin B is a heterodimer glycoprotein that downregulates follicle‐stimulating hormone and is produced predominantly by Sertoli cells. The potential correlation between changes in plasma Inhibin B and Sertoli cell toxicity was evaluated in male rats administered testicular toxicants in eight studies. Inhibin B fluctuations over 24 hr were also measured. METHODS Adult rats were administered one of eight testicular toxicants for 1 to 29 days. The toxicants were DL‐ethionine, dibutyl phthalate, nitrofurazone, 2, 5‐hexanedione, 17‐alpha ethinylestradiol, ethane dimethane sulfonate, hexachlorophene, and carbendazim. In a separate study plasma was collected throughout a 24‐hr period via an automatic blood sampler. RESULTS Histomorphologic testicular findings included seminiferous tubule degeneration, round and elongate spermatid degeneration/necrosis, seminiferous tubule vacuolation, aspermatogenesis, and interstitial cell degeneration. There was a varying response of plasma Inhibin B levels to seminiferous tubule toxicity, with three studies showing high correlation, three studies with a response only at a certain time or dose, and two studies with no Inhibin B changes. In a receiver operating characteristics exclusion model analysis, where treated samples without histopathology were excluded, Inhibin B showed a sensitivity of 70% at 90% specificity in studies targeting seminiferous tubule toxicity. CONCLUSION Decreases in Inhibin B correlated with Sertoli cell toxicity in the majority of studies evaluated, demonstrating the value of Inhibin B as a potential biomarker of testicular toxicity. There was no correlation between decreases in Inhibin B and interstitial cell degeneration. In addition, a pattern of Inhibin B secretion could not be identified over 24 hr.